How Does AI Improve Differential Diagnosis Generation? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) is rapidly transforming the healthcare landscape, and one of its most promising applications is in improving the generation of d...
Keywords: AI in Clinical Decision Support; Improve; Differential; Diagnosis; Artificial Intelligence; Machine Learning; Healthcare